Performance evaluation of potato genotypes for kharif cultivation in Odisha - Maharana, Jyotshnarani; Panda, C. M.; Dash, A. K.; Jakhar, Praveen (Annals of Agricultural Research, 2016)
An experiment was conducted to evaluate the performance of different potato genotypes for off- season cultivation in Koraput region of Odisha. Sixteen genotypes were evaluated for 10 quantitative characters during kharif season of 2014 and 2015 and their inherent relationship. Observation on plant height at 30 and 60 days after planting (DAP) revealed that Kufri Chipsona 3 recorded maximum plant height of 34.0 and 44.5 cm, respectively closely followed by Kufri Chipsona 1 (32.3 and 43.3 cm). For growth parameter leaf area, Kufri Lalit recorded maximum value of 111.3 cm2 statistically at par with Kufri Lalima (109.1 cm2 performed poorly with a meagre leaf area of 63.2 cm2 plant were recorded in Kufri Ashok (7.81), which was statistically at par with Kufri Lalima, Kufri Pukhraj, Kufri Lalit, Kufri Jyoti, Kufri Chipsona 3 and Kufri Khyati. Average tuber weight showed variation in kharif season potato in which variety Kufri Jyoti registered maximum value of 28.9, followed by Kufri Pukhraj (28.6) and Kufri Lalit (28.0). Kufri Lalima recorded maximum tuber yield of 133.2 q/ha which was statistically superior to all other varieties. Other promising varieties were Kufri Pukhraj, Kufri Lalit, Kufri Khyati, Kufri Jyoti and their performance were similar for tuber yield. Kufri Chipsona 3 performance was good with a yield of 120 q/ha while Kufri Arun registered a meagre yield of 84.2 q/ha. In terms of marketable yield, Kufri Pukhraj gave maximum yield of 107.4 q/ha which was at par to other top performers viz. Kufri Lalima, Kufri Lalit, Kufri Khyati and Kufri Jyoti. Potato marketable yield had positive and significant correlation with all other parameters except for plant height at 30 DAP. Other parameters viz. plant height at 60 DAP (0.446), total leaflets (0.391), dry matter (0.401), leaf area (0.794), tubers/plant (0.942) and average tuber wt. (0.735) exhibited higher values for genotypic correlation over phenotypic correlation. which was ) and Kufri Pukhraj (108.1 cm2 in kharif season. Maximum number of tubers/ ). Exotic variety ‘Atlantic’